Open Surgical Treatment versus Bulking Agents Injection by Endoscopy in Management of Vesicoureteral Reflux: A Comparative Study - حرفوش أيمن; يوسف محمد; حرفوش حسان (Latakia University Journal -Medical Sciences Series, 2020)
Background: The purpose of this study is to compare between open surgery and injection by endoscopy in management of vesicoureteral reflux and treating the urinary infection and the associated pyelonephritis. Materials and methods: The study started from January 2018 to January 2020 at Tishreen university hospital, Lattakia, Syria and achieved on 42 cases of vesicoureteral reflux at mean age of 4 years old divided into two groups. Open surgery was performed in 24 ureters whereas injection by endoscopy was performed in 18 ureters. Follow up was done by voiding cystourethrography after 3-6 months and urinalysis with ultrasound after 1 month. Results: Mean follow up was 12-15 months. The procedure was performed in 34 girls and 4 boys with highest old group 2-6 years. Success rate in open surgery was 87,5% with reflux recurrence in three patients whereas success rate was 94,4% in injection with reflux recurrence in one patient. Conclusion: The study shows up that there is a superiority of injection by endoscopy compared to open surgery in management of vesicoureteral reflux so we can approve injection as first line in treating due to it is a simple safe procedure done with less anesthesia time and needs less hospitalization.